P25 Feasibility cluster randomised controlled trial and process evaluation of an environmental intervention in nurseries and a web-based home intervention to increase physical activity, oral health and healthy eating in children aged 2–4 years: nap sacc uk. (2nd September 2017) - Kipping, RR; Langford, R; White, J; Metcalfe, C; Papadaki, A; Hollingworth, W; Moore, L; Campbell, R; Ward, D; Jago, R; Brockman, R; Wells, S; et al.
Abstract : Background: Systematic reviews have identified the lack of intervention studies to prevent obesity in young children. Most 3 year old children in the UK attend formal childcare, and the Government plans to extend free childcare to 30 hours per week for 3 and 4 year olds; therefore these settings present an opportunity to improve health. The Nutrition and Physical Activity Self Assessment for Childcare (NAP SACC) programme aims to improve child nutrition and physical activity through changes to the nursery environment. Feasibility and acceptability have been demonstrated through Randomised Controlled Trials (RCT) in the USA. This study examined the feasibility and acceptability of adapting the NAP SACC intervention for the UK. Methods: A feasibility cluster RCT in 12 nurseries with 2–4 year olds in the southwest region of England. Focus groups and interviews with Health Visitors (community children's nurses), nursery staff and parents informed adaptation of the intervention for the UK. The intervention comprised: two staff workshops on physical activity and nutrition; Health Visitor support to review nursery practices against 80 areas of best practice, set goals and make changes; a digital media-based home component. Measures were assessed at baseline and post-intervention: zBMI, accelerometer-measured physical activity and sedentary time, diet, child quality of life, health care usage, parental and nursery staff mediators and quality of nursery environment. Fidelity and acceptability were assessed through observation and interviews analysed via thematic analysis. Results: Formative work resulted in the following adaptations: inclusion of an oral health component; changes to confirm with UK guidance; specialist workshop facilitators; and development of the home component. 168 (37%) eligible children were recruited from 12 nurseries. Interviews were completed with four Health Visitors, 17 nursery staff and 20 parents. The intervention was implemented with high fidelity, with two exceptions: one nursery did not implement the intervention due to staff workload; and the digital home component was used by just 12 (14%) parents. Intervention acceptability was high. A mean of seven staff per nursery attended each workshop. The workshops and Health Visitor contact were highly valued. The mean number of goals set was eight. Nursery changes included: menu modifications, reducing portion sizes and sugary snacks, role modelling physical activity and eating, and active story telling. The trial design and methods were highly acceptable. Descriptive analysis of the outcomes will be available by September 2017. Conclusion: NAP SACC UK is feasible and acceptable with the exception of the home component; effectiveness should be tested through a full-scale RCT.